2023
DOI: 10.1039/d3dt00496a
|View full text |Cite
|
Sign up to set email alerts
|

9-Borafluoren-9-yl and diphenylboron tetracoordinate complexes of F- and Cl-substituted 8-quinolinolato ligands: synthesis, molecular and electronic structures, fluorescence and application in OLED devices

Abstract: Six new four-coordinate tetrahedral boron complexes, containing the 9-borafluoren-9-yl and diphenylboron cores attached to orthogonal fluorine- and chlorine-substituted 8-quinolinolato ligand chromophores, have been synthesised, characterised, and applied as emitters in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 128 publications
0
4
0
Order By: Relevance
“…The latter mechanism was recently suggested for related quinolate complexes based on the 9-bor-auorene core. 17 The DFT calculations (B3LYP/6-311++G(d,p)) of 3a-3g and 6a-6c revealed that the HOMO is localized on the diazabora-uorene scaffold whilst the LUMO is spread over the ligand (Fig. 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter mechanism was recently suggested for related quinolate complexes based on the 9-bor-auorene core. 17 The DFT calculations (B3LYP/6-311++G(d,p)) of 3a-3g and 6a-6c revealed that the HOMO is localized on the diazabora-uorene scaffold whilst the LUMO is spread over the ligand (Fig. 8).…”
Section: Resultsmentioning
confidence: 99%
“…The latter mechanism was recently suggested for related quinolate complexes based on the 9-borafluorene core. 17 …”
Section: Resultsmentioning
confidence: 99%
“…As a promising electroluminescent device, organic light emitting diodes (OLEDs) with a wide operating temperature range and a fast response time, are widely used in display and lighting applications. [1][2][3] In recent years, the design and research of OLED systems based on excited state proton transfer (ESPT) has become a research hotspot in the field of luminescence. 4,5 Because of the unique fast intramolecular four-level optical cycle between enol (N) and keto tautomers (T), fluorophores with ESPT characteristics are ideal low-energy emitters which can produce obvious double fluorescence emission phenomenon and minimize spectral overlap through great Stokes shift, thus effectively blocking energy transfer.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 These useful properties of organoboron compounds make them highly attrac-tive targets for a wide variety of photonic applications. [24][25][26] The instability of B-F bonds in boron-dipyrromethene (BODIPys) towards irradiation and solvent polarity has led researchers to focus towards TCOB complexes. 27 The B-O and B-N bonds of such TCOB molecules have a greater covalent character compared to the B-F bond found in the BODIPy class of fluorophores.…”
Section: Introductionmentioning
confidence: 99%